(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2020)
Proximate, minerals, vitamins, amino acids composition and phytochemicals of Moringa oleifera and Arachis hypogaea were investigated. The parameters evaluated were moisture contents; ash contents; crude protein; crude lipids; crude fiber; carbohydrates; mineral ions; vitamins; amino acids and phytochemicals. The results obtained showed that, all the proximate parameters, vitamins; A, C and E, all the phytochemical parameters and minerals; sodium and potassium are significantly different (p<0.05) while no significant different at p<0.05 was found in the amount of magnesium, potassium, iron, calcium and copper in M. oleifera and A. hypogaea. High caloric value was found in A. hypogaea while high amount of vitamin A and C were found in M. oleifera. Also, phytochemicals such as flavonoids and steroids were found in A. hypogaea at high amount. Eighteen amino acids were detected in both the M. oleifera and A. hypogaea. Glutamic acid, aspartic acid, leucine, arginine, valine, proline were present at high concentration in both the two samples.